Peeling The Onion: a study of audience reactions to anti-classism satire - Corsbie-Massay, Charisse L’Pree; Santia, Martina; Anderson, Luvell (Frontiers in Communication, 2026)
The topics of socioeconomic status, class, and income inequality are integral to human rights. However, media misrepresentation of socioeconomic class and the pervasive national narrative of social mobility inhibit audiences’ ability to understand and mobilize around these issues. Satire can disrupt this cycle by effectively exposing the inconsistencies of class inequality and the flaws of the “American Dream.” Thus, we examine the potential of satire to challenge prevailing attitudes toward class inequality and bolster anti-classism confidence through an online study featuring written satirical articles from The Onion categorized based on style (aggressive vs. benign) and target (individual vs. institutional). Overall, participants enjoyed the anti-classism satirical articles and exhibited more appreciation after repeated exposure. Satirical ratings were negatively correlated with legitimizing income inequality and positively correlated with confidence in disrupting hegemonic patterns regarding class inequalities. However, participants classification of the satirical targets did not align with the a priori categories established by the researchers. This work is some of the first to deploy content from The Onion, an American satirical staple, and explore the role of marginalization satire that tackles socioeconomic injustice.